Effect of the lemon essential oils on the safety and sensory quality of salted sardines (Sardina pilchardus Walbaum 1792). (March 2017) - Alfonzo, Antonio; Martorana, Alessandra; Guarrasi, Valeria; Barbera, Marcella; Gaglio, Raimondo; Santulli, Andrea; Settanni, Luca; Galati, Antonino; Moschetti, Giancarlo; Francesca, Nicola
Abstract: The main aim of this research was to investigate the biopreservative effects of lemon essential oil (EO) micro-emulsions on salted sardines. The experimental design included two experimental trials, SR1 and SR2 carried out with 25 ml of lemon EO micro-emulsion at 0.3 and 1.0% (v/v), respectively, and a control trial performed without EO addition. Chemical analyses on salted sardines inoculated with the EOs clearly showed a substantial persistence of several volatile organic compounds (VOCs) belonging to groups of monoterpene hydrocarbons, oxygenated monoterpenes and sesquiterpene hydrocarbons derived from EOs during the entire period of ripening. In particular, the molecules mostly represented were limonene, p-cymene and β-pinene. Immediately after the addition of EOs, the concentrations of all microbial groups decreased. The presence of Enterobacteriaceae, staphylococci and rod lactic acid bacteria (LAB) observed in the trials SR1 and SR2 was significantly lower than that registered for the control trial during the entire period of monitoring. Furthermore, the addition of EOs determined a lower accumulation of histamine in sardines compared to those of the control trial. The highest scores of sensory evaluation were registered for flavour and overall acceptability of the experimental trials in presence of EOs. On the basis of the increasing interest toward novel food preservatives, we conclude that the use of EOs to produce salted fishes represents a valid strategy to improve safety and sensory characteristics of salted sardines. This work has also economic implications, since the flavour improvement due to the addition of lemon EOs might increase the consumption of sardines by regular and new consumers. Highlights: Lemon essential oils as natural antimicrobial products. EO persistence during the entire period of ripening of salted sardines. EO addition improve safety and sensory characteristics of salted sardines.